Enzymatic Synthesis of High‐Density RNA Microarrays. Issue 2 (16th February 2023) - Schaudy, Erika; Lietard, Jory; Somoza, Mark M.
Abstract: Oligonucleotide microarrays are used to investigate the interactome of nucleic acids. DNA microarrays are commercially available, whereas equivalent RNA microarrays are not. This protocol describes a method to convert DNA microarrays of any density and complexity into RNA microarrays using only readily available materials and reagents. This simple conversion protocol will facilitate the accessibility of RNA microarrays to a wide range of researchers. In addition to general considerations for the design of a template DNA microarray, this procedure describes the experimental steps of hybridization of an RNA primer to the immobilized DNA, followed by its covalent attachment via psoralen‐mediated photocrosslinking. The subsequent enzymatic processing steps comprise the extension of the primer with T7 RNA polymerase to generate complementary RNA, and finally the removal of the DNA template with TURBO DNase. Beyond the conversion process, we also describe approaches to detect the RNA product either by internal labeling with fluorescently labeled NTPs or via hybridization to the product strand, a step that can then be complemented by an RNase H assay to confirm the nature of the product. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol : Conversion of a DNA microarray to an RNA microarray Alternate Protocol : Detection of RNA via incorporation of Cy3‐UTP Support Protocol 1 : Detection of RNA via hybridization Support Protocol 2 : RNase H assay